Domestic cat management in the UK: learnings from a global perspective - McDonald, Jenni L.; Hodgson, Dave J.; Roberts, Claire; Finka, Lauren; Halls, Vicky; Foreman-Worsley, Rae (Frontiers in Veterinary Science, 2025)
The overpopulation of domestic cats has the potential to result in negative outcomes for cats, people and the surrounding environment. A whole-population approach to management requires a system of services considering owned, shelter and free-living, unowned cats. Population management should also be considered at a localised level, with thought given to the unique populations of both cats and people in each environment. There is no simple, overarching solution to effective cat population management. Long-term management improvements require the addressing of root causes of overpopulation, rather than simply controlling the abundance of unowned cats. The role of rehoming organisations can be optimised by taking in only those cats that are suitable for rehoming and managing other unowned cats through community-level interventions. These approaches are beneficial for cat welfare, the welfare of cat carers and ultimately help more cats. Population processes, including reproductive output and survival of cats, and the carrying capacity offered by their environment, should also be critical considerations for the management of free-living, unowned cats. Compensatory effects, such as the movement of cats from neighbouring unowned or owned populations following population declines due to trap-neuter-return or rehoming, may contribute to the limited success of management programs. Education of cat carers around feeding and its effect on local carrying capacity is likely to be a valuable component of population management. Unrealistic expectations for the success of population management will be mitigated via better understanding of the population processes of domestic cats and of the attributes, attitudes and behaviours of people within local communities. It can take time for population numbers to reduce meaningfully via natural-cause mortality, and short-term population reductions can be misleading as populations may return due to compensatory processes. This wider understanding both within affected communities and for those actively participating in management is critical to developing practical solutions with realistic outcomes. Indeed, where there are owned cats or neighbouring free-living, unowned cats, then population management should be considered a permanent range of services that need to be sustained and adapted over time.